Efficacy of firm size and structure on organizational performance - OLALEKAN OWOTUTU SABITU; SOLOMON AKPOVIRORO; Sodeinde Gbemi (Економіка та управління АПК, 2024)
Firm size plays an important role in determining firm’s performance even though it’s not clear whether firm size affect organizational perfor[1]mance. Therefore; an investigation is required to assess the effect firm size and structure will have on firm’s performance. The specific objectives were to investigate the relationship between firm size and firm performance and to analyze the relationship between organizational structure and firm per[1]formance. For the purpose of this study primary data was used. The ex[1]post facto method was employed. The population consists of the members of staff of Guinness International PLC Plant, Lagos Nigeria. Yamane for[1]mula was adopted to determine the sample size. The data was analyzed us[1]ing manual and electronic based methods through the data preparation grid and statistical package for the social sciences, (SPSS). Linear regression analysis method which also makes use of ANOVA was employed to test the hypothesis. The findings of this study have shown a positive relation[1]ship between firm size and competitive advantage such that competitive advantage is affected by firm size. A finding from the study also shows that there is significant relationship between organizational structure and firm performance. It was concluded that strategic factors cannot be overempha[1]sized in determine the size, structure and performance of firm. This study has made us understand the effect of strategic factor on firm performance and also revealed immense benefit to both local and international firms as well as useful to students for further research. This study will make orga[1]nizations to understand the effect of strategic factor on firm performance and it will also be of immense benefit to both local and international firms as well as useful to students for further research. It will help management and manager to identify the effect of strategic factors on firm performance. The study will give more insight into the relationship between strategic factors and firm performance for academician.